Application of Multivariate Statistics for the Development of a Water Quality Model of Estuary El Macho, Machala-Ecuador - Zhindon-Almeida, Rafael Gilberto; Sánchez-Ancajima, Raúl Alfredo; Castañeda-Guzmán, Walter Javier (Journal of the University of Zulia, 2023)
Water is an essential element for people, as well as for sustaining life on the planet. In this way, due to the contamination that water can suffer from a chemical or biological type, it is necessary to have knowledge about its availability based on its quality characteristics. Consequently, statistical models are the relevant means to carry out an evaluation and future estimates about the quality of surface waters. Therefore, the present work is aimed at formulating a statistical model that allows determining the degree of contamination of the waters of the El Macho estuary, located in the city of Machala, province of El Oro. The applied methodology was of a basic type, since a search of theoretical foundations was carried out that allows to deepen in the statistical modeling for studies of water quality. The research design is correlational under a multivariate statistical model of multiple linear regression. The unified multiple linear regression model concluded that the biochemical oxygen demand significantly determines the water quality of the estuary, according to the chemical parameter, chemical oxygen demand and the physical parameter total dissolved solids. The coefficient of determination indicates that these variables explain 99.9% of the variation of the dependent variable.